In vitro efficacy of Morinda citrifolia l in the control of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Nápoles V., Darién (2017)
The aim of this study was to evaluate the in vitro efficacy of Morinda citrifolia L in comparison with conventional chemical products (Supatraz®/amitraz and Ticomín®/ cipermetrina) on engorged females of Rhipicephalus (Boophilus) microplus. The adult ticks were collected from cattle free of chemical acaricides. Ten ticks were selected per Petri dish (n=24) and distributed in 8 treatments with 3 replicas each one. Treatments T1 to T5 received hidroalcoholic solutions of Morinda citrifolia L at 10, 5, 2.5, 1.25 y 0.625% respectively; T6 received Supatraz®/amitraz and T7 Ticomín®/Cipermetrina in 1:1000 dilution; and T8 was the negative control (distilled water) in volumes of 15 ml per Petri dish for 5 min. The readings were carried out at 15 min and 24 h postexposition. Dead ticks were counted to determine the efficacy of the treatments. The results showed an efficacy of 89.6 and 41.3% for the chemical treatments T6 and T7, whereas the maximum efficacy for M. citrifolia L was 20.6 in the concentration of 10%.